Determinants of Financial Reporting Quality in Local Government Agencies: Evidence from Post-WTP Langsa City, Indonesia - Rafli Aditya Pratama; Nasrul Kahfi Lubis; Nurliza Lubis (Journal of Management and Business Innovations, 2025)
This study analyzes determinants from financial reporting information quality in Regional Government Organizations (OPD) of Langsa City, Indonesia. Despite consistently obtaining an Unqualified Opinion (WTP) from Audit Board of Indonesia, audit findings still reveal weaknesses in internal control and revenue management, indicating a gap between audit opinions and actual reporting quality at the operational level. This study detects this breach by examining the effects from human resource competence, internal control systems, and transparency. Utilizing a quantitative approach, data were accumulated from 72 financial officers across 36 OPDs and assessed utilizing multiple linear regression. The outcomes stipulate that human resource competence is the most influential determinant, while transparency shows a positive but marginal effect. Internal control systems exhibit a statistically significant yet very weak contribution. Simultaneously, all variables significantly affect financial reporting quality, although the explanatory power from model remains limited. The novelty from this study sits in demonstrating that WTP status does not necessarily reflect strong operational-level financial reporting quality. Policy implications emphasize improving accounting competencies, strengthening effective internal control implementation, and enhancing transparency to support more accountable local government financial reporting. Keywords: Financial Reporting Quality, Human Resource Competence, Internal Control System, Local Government, Transparency